Morphological quality of natural post-fire regeneration of Pinus douglasiana Martínez from Southern Oaxaca - Aquino-López, Rosario; Castañeda-Hidalgo, Ernesto; Rodriguez Ortiz, Gerardo; Santiago-Martinez, Gisela Margarita; Lozano Trejo, Salvador (Ecosistemas y Recursos Agropecuarios, 2023)
T The natural regeneration of post-fire pine depends on various factors, such as plant quality from obtaining plants with desirable morphological characteristics that allow better expectations of survival and growth. The objective was to evaluate the quality of P. douglasiana regeneration in areas with different fire severity. In 2022, destructive sampling was carried out on two-year-old plants to determine the quality of the plants. The level of severity and morphological quality were differentiated through analysis of variance and means comparison test (Dun- can, 0.05). The results show significant differences between the level of fire severity (p ≤ 0.05) for the quality indices of height, leaf biomass, root, aerial biomass, total biomass, height ratio and root length. For root length, stem biomass, aboveground biomass and root biomass ratio and Dickson index, no significance was found (p > 0.05). According to the root height and length relationship, lignification index and Dickson index, good plant quality was presented at the three levels of fire severity. For aboveground biomass, underground biomass and slenderness index, the plants showed low quality. The highest ratios in diameter (4.15mm), height (26.03 cm), leaf area (321.2cm2) and total biomass (5.84 g) were obtained for the high severity area. The burned areas are suitable for natural regeneration and are improved if they are combined with forestry activities that improve their quality in the future.